Peningkatan Minat Belajar Ipa Melalui Strategi Word Square Pada Siswa Kelas V Di SD Negeri 03 Malanggaten Kebakkramat Karanganyar Tahun Ajaran 2015/2016 - Prasetyo, Tedy Bagus Adi, Dr. Achmad Fathoni, S.E., M.Pd (2016)
The purpose of this study to describe that word square strategy can increase student interest class V SD Negeri 03 Malanggaten. Research is a Classroom Action Research (CAR), which implemented the collaboration between classroom teachers with researchers. Subjects in this study were teachers and students. Teachers as the subject of the perpetrator and the student as a subject the recipient action. This research was conducted in two cycles and each cycle consisting of two meetings. . The validity of the data used to use triagulasi data and techniques triagulasi. Technical analysis of the data used is data analysis techniques with reduction, presentation, verification. The research result of this class action is an increase in student interest in learning science. It can be seen from the indicators of achievement of learning interest include: pleasure, attention and engagement in learning activities that increase. The percentage of student interest in learning who delighted in learning activities in the pre-cycle by 35%, in the first cycle of 60%, and the second cycle by 90%, while the students paid attention in learning activities in the pre-cycle by 45%, in the first cycle of 65%, and the second cycle by 85%. While students who are actively involved in learning activities in the pre-cycle by 40%, in the first cycle of 65%, and the second cycle by 80%. This study concluded that the implementation of the strategy Word Square can improve the learning interest in science teaching fifth grade students of SD Negeri 03 Malanggaten Academic Year 2015/2016.